2006
DOI: 10.1074/jbc.m510851200
|View full text |Cite
|
Sign up to set email alerts
|

Model of Biologically Active Apolipoprotein E Bound to Dipalmitoylphosphatidylcholine

Abstract: Apolipoprotein (apo)E plays a critical role in cholesterol transport, through high affinity binding to the low density lipoprotein receptor. This interaction requires apoE to be associated with a lipoprotein particle. To determine the structure of biologically active apoE on a lipoprotein particle, we crystallized dipalmitoylphosphatidylcholine particles containing two apoE molecules and determined the molecular envelope of apoE at 10 Å resolution. On the basis of the molecular envelope and supporting biochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
103
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(115 citation statements)
references
References 40 publications
11
103
0
1
Order By: Relevance
“…Lipidation of apoE and its domains has only a small effect on the affinity for apoC-II fibrils, suggesting that there is limited structural change in apoE at the sites of interaction. This is consistent with models of lipoprotein-bound apoE, which suggest that helix three is curved around the lipoprotein surface, with the hydrophobic face interacting with the lipid surface (54,55). This conformation would still allow basic residues on helix three of apoE to interact with alignments of negative charges on amyloid fibrils as shown in Fig.…”
Section: Discussionsupporting
confidence: 74%
“…Lipidation of apoE and its domains has only a small effect on the affinity for apoC-II fibrils, suggesting that there is limited structural change in apoE at the sites of interaction. This is consistent with models of lipoprotein-bound apoE, which suggest that helix three is curved around the lipoprotein surface, with the hydrophobic face interacting with the lipid surface (54,55). This conformation would still allow basic residues on helix three of apoE to interact with alignments of negative charges on amyloid fibrils as shown in Fig.…”
Section: Discussionsupporting
confidence: 74%
“…Biochemical studies have shown that R172, a residue disordered in the structure of the lipid-free N-terminal domain, makes an important contribution to high-affinity receptor binding [23]. A model based on the 10 Å-resolution x-ray diffraction data, combined with this and other biochemical observations, suggest that R172 is repositioned close to the 140-160 helix to create the receptor-binding epitope [21]. Electron paramagnetic resonance studies of ApoE using site-directed spin labels incorporated into a series of single cysteine substitution variants surrounding R172, together with fluorescence studies using an environmentally sensitive probe, also argue that lipid association induces a structural transition of this region of the protein from random coil to alpha helix and relocation to a more hydrophobic environment, again supporting the notion that lipid interaction triggers a crucial structural transition around R172 that enables high-affinity receptor binding [24].…”
Section: Apolipoprotein Recognitionmentioning
confidence: 84%
“…The 10 Å-resolution crystal structure of a receptor-binding active ApoE-dipalmitoyl phophatidylcholine particle [21], together with more recent analysis of similar particles in solution by small angle X-ray scattering [22], shows that lipid induces global rearrangements of the helices that comprise the receptor-binding domain (Figure 4). Biochemical studies have shown that R172, a residue disordered in the structure of the lipid-free N-terminal domain, makes an important contribution to high-affinity receptor binding [23].…”
Section: Apolipoprotein Recognitionmentioning
confidence: 98%
See 1 more Smart Citation
“…To date, apolipoprotein structures are available of the 22-kDa N-terminal domain of human/mouse apoE (14 -16), ⌬(1-43)apoAI (17) and of three intact apolipoproteins, apoAI (18), insect LpIII (19,20), and apoAII (21), all in the lipid-free state. In the lipid-bound state, only recently the first low resolution (10 Å) x-ray model has been reported of an intact apolipoprotein, apoE (22). Also reported is the three-dimensional structure and dynamics of apoCII bound to micelles derived from NMR relaxation data (23).…”
mentioning
confidence: 99%